Persepsi Mahasiswa terhadap Program Beranda Dakwah Spesial Ramadhan 2025 - FIRMANSYAH, EDY; DAMARYAM, WULAN; ZAKIYAH, HAFIDZATUZ; ., RISKAYANTI (Nubuwwah : Journal of Communication and Islamic Broadcasting, 2026)
This study aims to understand students’ perceptions of the “Beranda Dakwah Spesial Ramadhan 2025” program organized by UINSI TV, an initiative of FUAD students. This research employed a descriptive qualitative approach using semi-structured interviews with three students of the Islamic Communication and Broadcasting Study Program as key informants. Data were analyzed thematically through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that students had positive perceptions of the program. The preaching materials were considered relevant, concise, and suited to students’ needs. The speakers’ delivery was also viewed as clear, communicative, and easy to understand. The program positively impacted students’ consistency in worship, motivation to deepen religious knowledge, and spiritual awareness. This study confirms that digital da’wah programs adapted to the characteristics of young audiences are effective in strengthening students’ spiritual and intellectual development and should be sustainably implemented beyond the month of Ramadan.